Systematics Literature Review: Mathematics Reasoning in Elementary School - Hs, Atika Maulidina; Wiryanto, Wiryanto; Mariana, Neni (LPPM Universitas Trunojoyo Madura, 2023)
Based on data from PISA, it shows that students' mathematical abilities in Indonesia are still relatively low. Therefore, improving students' mathematical reasoning abilities is a way in order to cope with those problems. This research aims to analyze research related to the mathematical reasoning abilities of elementary school students in 2018-2022, considering that a literature review on this topic has never been carried out. The type of this research is a systematic literature review. Data was collected by documenting 20 selected articles in Sinta 1-6 journals and Scopus. The results of this research revealed that topics related to mathematical reasoning abilities in elementary schools have not been widely researched in the last five years. The majority of articles discuss the characteristics and the analysis of students' reasoning abilities mapping in a group. The most widely published Sinta 3 and Scopus articles with the most researched material are geometry. The frequent type of research carried out is quantitative. Suggestions for future research are to conduct further research related to the development of mathematical reasoning abilities in elementary schools, especially on fractions and algebra materia.